Incorporation of holistic and spiritual approach in geriatric care - sharing experience at Rumah Ehsan - Shalihin, Mohd Shaiful Ehsan; Kating, Zuraini; Aidid, Edre; Mohamad Zahir, Mohd Zulkifli; Wan Mamat, Wan Hasliza (AL-QIYAM Centre for Scientific Research and Studies, 2022)
The geriatric population is increasing in trend worldwide. Therefore, more morbidities would be expected to occur and be detected, including deterioration of cognitive health among the older population. Dementia will cause a reduced quality of life for the patient and their caretaker. Nevertheless, if the disease is detected earlier in its pre-clinical phase, known as mild cognitive impairment, the disease progression can be stopped with adequate holistic management consisting of biological, psychological, social, and spiritual approaches. Spiritual care in fact provides an essential role with regard to mental health among geriatric patients. This aspect of care must be taught to medical staff, especially in geriatric facilities like Rumah Ehsan. This study aims to incorporate the holistic approach including spiritual input in screening and managing geriatric patients among staff at Rumah Ehsan. The knowledge and practise skills have been transferred well to the whole staff in this Knowledge Transfer Program for a 12-month duration. All geriatric patients have received the benefit and have been screened and managed successfully. The Paired Sample t test proved that there was a significant increase in marks received by staff with regards to all theoretical knowledge components given to patients (p 0.05). 6.8% of patients were noted to have cognitive impairment, and none of them developed worsening symptoms due to the successful intervention under this program. Indeed, this programme reflects the successful incorporation of holistic, specifically spiritual elements, into patient care.